Hematokolpos dan Hematometra Sekunder Akibat Himen Imperforata: Diagnosis dan Tata Laksana - Firda Fairuza (Jurnal Biomedika dan Kesehatan, 2022)
BackgroundImperforate hymen is an uncommon congenital anomaly of the female genital tract and is rarely diagnosed in newborns. An imperforate hymen is a cause of primary amenorrhea. Case DescriptionA 12-year-old girl was admitted to the pediatric outpatient clinic with cyclic abdominal pain for eight days. She had lower abdominal pain with dysuria and constipation for the previous six weeks. There is a bulging mass on the perineal that appears when straining. Fever, nausea, vomitus, abdominal enlargement, and leucorrhea were denied; breast enlargement since 12 years old with no history of menarche. The patient vital signs were normal. On physical examination obtained, lower abdominal pain and tender suprapubic mass were palpable. The pubertal status was normally secondary sexual characteristics. An interlabial mass was found protruding from the introitus vagina and the hymen intact on inspection of the external genitalia. Laboratory and urinalyses revealed normal. Hematometra and hematocolpos were found on abdominal ultrasonography, which led to the diagnosis of imperforate hymen. Therefore, a hymenectomy was performed and evacuated 520 ml of dark red blood. The patient’s condition was good, and she had regular menstruation. ConclusionsImperforate hymen is an easy diagnosis, but sometimes clinicians are oblivious to including this in the differential diagnosis of lower abdominal pain in pubescent girls with primary amenorrhea. Also, a lack of awareness about the importance of external genitalia examination as part of routine physical examination in children and adolescents makes this diagnosis easily missed or delayed.